Study guides

☆☆

Q: Factor 3ab plus 3ac plus 2b2 plus 2bc?

Write your answer...

Submit

Still have questions?

Related questions

3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)

(3a - 2c)(b - d)

(a+b)(3b+1)

(3b - 1)(a - b)

6

12ab+3ab=15ab

(3b - 1)(a - b)

3ab - a - 3b2 + b = -3b2 + 3ab + b - a = -3b(b - a) + 1(b - a) = (1 - 3b)(b - a)

Factorizing 3ab + 3ac gives 3a (b + c).Factorizing is to express a number or expression as a product of factors.When factorizing always look for common factors. To factorize (3ab + 3ac) look for the highest factor between the two terms (3a). 3ab + 3ac = 3a (b + c)

-2ab

It is: 3ab

Provided multiplication is commutative, it is 8ab.

It is an algebraic expression because it has no equality sign.

2a-3ab = -1

3ab x 2c = 6abc

(a+b)3=a3+b3+3ab(a+b) a3+b3=(a+b)3-3ab(a+b) a3+b3=(a+b)(a2-ab+b2)

GCF(6a2bx, 15ab2x-24ab) = GCF[6a2bx, 3ab(5bx-8)] = 3ab

8ab

5ab-2ab+4a-b+5b = 3ab+4a+4b

10ab-9

Assuming that non-leading numbers are exponents, the expression becomes12a^2b + 8a - 5a^2b + 2ab - 4ab^2 + 6ab - 2a - 3ab= 7a^2b + 6a + 5ab - 4ab^2= a*(7ab + 6 + 5b - 4b^2)

(a+b)cube = a cube + b cube + 3a square b + 3ab square

3ab

-1

(3ab)^(2) Explanation: Simplify (3ab)^2 Use the power rule (ab)^n = a^nb^n to distribute the exponent. Raise 3 to the power of 2. 9a^2b^2